Preparation Technique and EMI Shielding Evaluation of Flexible Conductive Composite Fabrics Made by Single and Double Wrapped Yarns. Issue 4 (December 2017) - Lou, Ching-Wen; Li, Ting-Ting; Hwang, Po-Wen; Chen, An-Pang; Lin, Jia Horng
Electronics products and communication equipment release electromagnetic (EM) waves in service. EM waves affect biological health and precision instrument accuracy. This study purposes to fabricate flexible conductive composite fabric which is made of complex yarn using metal (stainless steel, copper) fibers and PET filaments. Complex yarn is formed by a rotor twisting machine, at varying values of wrapped number (6.5-16 turns/cm) and lamination number (single-layer, double-layer). Results show that when the complex yarn was wrapped 16 turns/cm, volume resistivity reached 2.9 Ohm-cm and conductivity reaches 0.408 S/cm. Four layers of conductive composite plied with 0°/90°/ 0°/ 90° resulted in the optimum electromagnetic shielding effectiveness, up to 47.7 dB.